IFIP the International Federation for Information Processing
DOI: 10.1007/978-0-387-74161-1_16
|View full text |Cite
|
Sign up to set email alerts
|

Patient Fall Detection using Support Vector Machines

Abstract: This paper presents a novel implementation of a patient fall detection system that may be used for patient activity recognition and emergency treatment. Sensors equipped with accelerometers are attached on the body of the patients and transmit patient movement data wirelessly to the monitoring unit. The methodology of support Vector Machines is used for precise classification of the acquired data and determination of a fall emergency event. Then a context-aware server transmits video fi-om patient site properl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 14 publications
0
46
0
Order By: Relevance
“…Another research area that benefits from the utilisation of wearable sensors is health care, where people presented their work on automatic fall detection [8,36]. As expected, also in these experiments, the data collection was carried out in a controlled environment where participants imitate falling.…”
Section: Related Work 21 Action Recognition With Accelerometersmentioning
confidence: 97%
“…Another research area that benefits from the utilisation of wearable sensors is health care, where people presented their work on automatic fall detection [8,36]. As expected, also in these experiments, the data collection was carried out in a controlled environment where participants imitate falling.…”
Section: Related Work 21 Action Recognition With Accelerometersmentioning
confidence: 97%
“…4 can be combined with sound data classification in order to achieve improved human monitoring and activity recognition. Previous studies found in literature [30][31][32] have proved the feasibility of distinguishing movement types and indicating patient falls by utilizing solely motion data. However, the combination of sound data can improve accuracy as indicated in the following section.…”
Section: Motion and Sound Data Mergingmentioning
confidence: 99%
“…Based on previous work [30][31][32], a cascading architecture of Support Vector Machines (SVMs) has been selected for motion data classification and fall detection. SVMs is a popular algorithm for data classification into two classes [33,34] that allows the expansion of the information provided by a training data set as a linear combination of a subset of the data in the training set (support vectors).…”
Section: Advanced Data Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Doukas et al [26] applied the sensor to the patient's foot in order to transmit patient movement data wirelessly to the monitoring center. The center generalizes data in the three axis and uses machine learning method to classify an event a fall or not.…”
Section: Related Workmentioning
confidence: 99%